Local Fuel Starvation Degradation of an Automotive PEMFC Full Size Stack. Issue 4 (21st April 2020) - Obermaier, M.; Rauber, M.; Bauer, A.; Lochner, T.; Du, F.; Scheu, C.
Abstract: The achievement of durability targets is an important challenge for the commercialization of fuel cell electric vehicles (FCEV). In order to meet the requirements, knowledge about the most severe degradation mechanisms of fuel cell stacks under automotive conditions is crucial. In the present work, degradation analysis of an automotive full size stack is performed. Herein, we focus on defects at the cathode catalyst layer and their interrelation including inhomogeneous adhesion of the microporous layer on the catalyst layer, crack formation, cathode catalyst layer thinning and wrinkling of the catalyst coated membrane. In addition, we report linear and circular Pt depositions on top of the cathode catalyst layer, which have to the best of our knowledge not been described in literature yet. For the latter, a degradation mechanism based on liquid water formation, local fuel starvation and current density distribution at the interface between microporous layer and cathode catalyst layer is postulated. Finally, a fast indication for stack degradation is suggested by correlating different degradation phenomena. This improved stack analysis approach allowed us to detect local differences in degradation on both cell and stack level.